El sistema de rehabilitación social y su incidencia en el proceso de reinserción en el CPL del cantón Guaranda 2020. - Gaibor Bósquez, Jeimy Dayanara (2023)
The prison reality that Ecuador is going through is the result of a deficient public policy, because although it is true that the laws and regulations exist, their application does not take place in the way that has been planned, being on the one hand the shared responsibility of those who develop these projects, since they have not made a prior study of budget or scope, as well as of the execution and control bodies of compliance with rehabilitation policies. And it is that, social rehabilitation should not only be understood as the legal institution that seeks to generate a change in the individual subject to the stimulus of the deprivation of liberty, but should be aimed at encompassing the fundamental aspects, such as protection and the exercise of their rights, so that, within the prisons, a favorable environment is generated that allows those deprived of liberty to have a dignified life, so that when they serve their sentence, social reintegration takes place in the best way. On the other hand, we must take into account that the main purpose of the custodial sentence, which is to develop new capacities in the individual who has been subjected to this stimulus, but the public policy of social rehabilitation has made these postulates only are mere statements, because in reality prison programs have become a means of coercion, but not reeducation, where institutional problems have a great impact, in that a person cannot readapt to the social environment when he completes his sentence, much less make it stop recurring. That is why in this research a methodology with an exploratory and correlational scope has been used, which will be supported by a quantitative approach; seeking to respond legally as the process of social rehabilitation of adults in conflict with the law of the Center for Deprivation of Liberty of the canton Guaranda, Province of Bolívar affects the process of social reintegration.